Prenatal Depression, Breastfeeding, and Infant Gut Microbiota - Rodriguez, Nicole; Tun, Hein M.; Field, Catherine J.; Mandhane, Piushkumar J.; Scott, James A.; Kozyrskyj, Anita L. (Frontiers in Microbiology, 2021)
Depressive symptoms are common during pregnancy and are estimated to affect 7–20% of pregnant women, with higher prevalence found in those with a prior history of depression, in ethnic minorities, and those with increased exposure to stressful life events. Maternal depression often remains undiagnosed, and its symptoms can increase adverse health risks to the infant, including impaired cognitive development, behavioral problems, and higher susceptibility to physical illnesses. Accumulating research evidence supports the association between maternal physical health elements to infant gut health, including factors such as mode of delivery, medication, feeding status, and antibiotic use. However, specific maternal prenatal psychosocial factors and their effect on infant gut microbiota and immunity remains an area that is not well understood. This paper reviews the literature and supplements it with new findings to show that prenatal depression alters: i) gut microbial composition in partially and fully formula-fed infants at 3-4 months of age, and ii) gut immunity (ie. secretory Immunoglobulin A) in all infants independent of breastfeeding status. Understanding the implications of maternal depression on the infant gut microbiome is important to enhance both maternal and child health and to better inform disease outcomes and management.